Brain temperature and its role in physiology and pathophysiology: Lessons from 20 years of thermorecording. Issue 4 (2nd October 2019) - Kiyatkin, Eugene A.
ABSTRACT: It is well known that temperature affects the dynamics of all physicochemical processes governing neural activity. It is also known that the brain has high levels of metabolic activity, and all energy used for brain metabolism is finally transformed into heat. However, the issue of brain temperature as a factor reflecting neural activity and affecting various neural functions remains in the shadow and is usually ignored by most physiologists and neuroscientists. Data presented in this review demonstrate that brain temperature is not stable, showing relatively large fluctuations (2-4°C) within the normal physiological and behavioral continuum. I consider the mechanisms underlying these fluctuations and discuss brain thermorecording as an important tool to assess basic changes in neural activity associated with different natural (sexual, drinking, eating) and drug-induced motivated behaviors. I also consider how naturally occurring changes in brain temperature affect neural activity, various homeostatic parameters, and the structural integrity of brain cells as well as the results of neurochemical evaluations conducted in awake animals. While physiological hyperthermia appears to be adaptive, enhancing the efficiency of neural functions, under specific environmental conditions and following exposure to certain psychoactive drugs, brain temperature could exceed its upper limits, resulting in multiple brain abnormalities and life-threatening health complications.